Firm resources, competitive actions and performance: investigating a mediated model with evidence from the in‐vitro diagnostics industry - Ndofor, Hermann Achidi; Sirmon, David G.; He, Xiaoming (Strategic Management Journal, 2011)
Abstract Building on the resource‐based view (RBV) and competitive dynamics literatures, this paper proposes that considering resources or actions independently offers an incomplete understanding of the drivers of superior performance. Instead, we hypothesize that resources enable competitive actions and that when these actions leverage the firm's resources, superior performance results. We tested these hypotheses with panelized data on the technological resources and competitive actions of firms in the in‐vitro medical diagnostic substance manufacturing industry. The results provide substantial support for our hypotheses, specifically with respect to mediation. Our theory and results underscore how the integration of the competitive dynamics and RBV literatures can significantly improve our understanding of firm performance. Copyright © 2011 John Wiley & Sons, Ltd.